Human Resource Management and Employee Experience on Implementing a Novel Teleconsultation Service at a Small Private General Practice Clinic in Bali, Indonesia: A Qualitative Study - Gustina, Ni Luh Zallila; Rinawati, Rinawati; Wirawan, Gede Benny Setia (International Journal Administration, Business & Organization, 2025)
This qualitative study explores the perceptions of clinic staff regarding their experiences with teleconsultation services and the human resource management (HRM) aspects involved in implementing such services in a small general practice (GP) clinic in Bali, Indonesia. The clinic operates a unique model where nurses manage patient care during morning shifts with remote physician support via teleconsultation. Data were collected through an online long-form survey completed by nine current and former staff members, including nurses and physicians. Thematic analysis revealed that teleconsultation was widely perceived as improving efficiency and accessibility of care. However, participants also reported challenges such as communication gaps, technical limitations, and diagnostic constraints. All respondents emphasized the need for structured training, adequate infrastructure, and clear communication protocols. While most participants expressed satisfaction with the service, this was closely linked to the availability of support and the nature of patient interaction. The findings underscore the importance of comprehensive HRM strategies that address both technical and interpersonal dimensions to ensure the sustainability and effectiveness of teleconsultation services in small clinical settings